2016
DOI: 10.1002/sdtp.10920
|View full text |Cite
|
Sign up to set email alerts
|

76-3: Development of a Top-Gate Transistor with Short Channel Length and C-Axis-Aligned Crystalline Indium-Gallium-Zinc-Oxide for High-Resolution Panels

Abstract: We have fabricated top‐gate field‐effect transistors (FETs) based on an oxide semiconductor for high‐performance driving capability. The optimization of the plasma treatment enabled a 50‐nm‐thick gate insulating film and a short channel length of these FETs, enabling a high FET performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously developed OS FETs with back-channeletched (BCE) and top-gate self-aligned (TGSA) structures [1][2][3][4][5][6]. BCE OS FETs can be fabricated using fewer masks than those required for TGSA OS FETs.…”
Section: Introductionmentioning
confidence: 99%
“…In the authors' previous study, high-mobility IGZO with In:Ga:Zn ratio = 4:2:3 (IGZO(4:2:3)) was prepared and high field-effect mobility and reliability were achieved using IGZO(4:2:3) [4][5][6][7]. Ito et al recently reported high-mobility IGZO with a Hall mobility of 50 cm 2 /Vs [8].…”
Section: Introductionmentioning
confidence: 99%